Peran Etika Manajemen Terhadap Kualitas Lembaga Pendidikan - Syafri Fadillah Marpaung; Fazli Abdillah; Hasana Fadilla (Peneliti.net, 2023)
The low quality of education in Indonesia is actually a discussion that has existed for a long time. However, until now the problem of education quality has not been resolved. Quality education is the hope and demand of all education stakeholders. Everyone will certainly prefer to study at institutions that have good quality. On this basis, schools/educational institutions must be able to provide good service and quality so that they are not left behind and are able to compete with other educational institutions. The data collection technique used in this research is a literature study technique where this research is conducted by collecting data related or relevant to research originating from scientific journals and other publications that are worthy of being a research source. The results of this study indicate that ethics and responsibility in business have the same role which aims to improve the image of educational institutions to develop schools. An educational institution will be hampered or unable to develop without the role of good management ethics.